Gerakan Penghijauan Sebagai Rintisan Desa Wisata Untuk Meningkatkan Income Masyarakat Di Desa Sumokali, Candi, Sidoarjo - Imamah, Nurul (Universitas Hasyim Asy'ari Tebuireng Jombang, 2021)
The reforestation movement through planting 100 red shoots is the first step towards a tourist village that will have a positive impact on the village community. If this program is implemented properly and can be followed by the local community, the tourism village program will be achieved. Education of the reforestation movement in order to increase the income of the Sumokali village community towards a tourist village with the target of MSMEs, PKK groups and Youth Organizations. The team planned several programs related to this theme and implemented them by complying with strict health protocols because currently the Covid-19 pandemic is still in progress. This community service program is expected to achieve the objectives of the theme, which is to help increase community income through existing Micro, Small and Medium Enterprises (MSMEs) by providing socialization, training and implementation of the program. The program implementation method is carried out in several stages, including: 1) the preparation stage; 2) implementation stage; 3) evaluation stage. The results of the implementation of this community service program is implementing the planting of 100 red shoots. Furthermore, the success of the tourism village program can increse income dan help improve the quality of the environment in Sumokali village so as to create a healthy community as a supporter of the tourism village program and increase community income through MSMEs.